PENGEMBANGAN E-MODUL PEMBELAJARAN KOMPETENSI PEMESINAN BUBUT UNTUK PEMBELAJARAN DARING SISWA KELAS XI SMK MUHAMMADIYAH 3 YOGYAKARTA: Pengembangan, e-modul, pemesinan bubut. - setiawanawan323 Awan setiawan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
Developing a Lathe-Machining Competency Learning E-module for the Online Learning of Eleventh Grade Students at SMK Muhammadiyah 3 Yogyakarta. A Thesis of Mechanical Engineering Vocational Education Study Program, Faculty of Teacher Training and Education, Sarjanawiyata Tamansiswa University, Yogyakarta” 2021. This “research intended to: (1) Develop steps of a Lathe-Machining Technique E-module for Eleventh Grade Students at SMK Muhammadiyah 3 Yogyakarta; (2) Distinguish the feasibility of the created Lathe-Machining Technique E-module for Eleventh Grade Students at SMK Muhammadiyah 3 Yogyakarta. (3) Distinguish the effectiveness of the developed Lathe-Machining Technique E module for Eleventh Grade Students at SMK Muhammadiyah 3” Yogyakarta. This research “was Research and Development (R&D). The research design used in this research was of ADDIE that consisted of five steps, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The research instrument was questionnaires to collect the data. The research subjects of this research were the material expert, the media expert, and the students to get an assessment and response to the feasibility of the e-module. The data analysis technique used in this research was quantitative descriptive” analysis. The result showed that Lathe-Machining Technique E-module was appropriate and proven by the material expert's assessment score for obtaining a feasibility level of 4.44 “with a very feasible category. According to the media expert, the feasibility of the e-module got a feasibility level of 4.25 with a very feasible category. The response from students at SMK Muhammadiyah 3 Yogyakarta was 4.69 with a very feasible category. The research showed that Lathe-Machining Technique E-module was appropriate to use online learning at SMK Muhammadiyah” Yogyakarta.